(untitled) (Communication & Society, 2023)
Combining computational methods with qualitative analyses, this research explores how the European Union (EU) employed digital diplomacy to manage its reputation during the COVID-19 pandemic. To this end, it addresses two influential dimensions of digital diplomacy: narratives and social networks. First, to identify how narratives evolved during the different phases of the crisis, dynamic topic modeling is applied to a sample of 12,935 tweets in English published by eight central EU authorities from January 1st, 2020, to March 11th, 2021. The most representative tweets of the six most predominant topics on COVID-19 are analyzed through the strategic narratives’ framework. Second, a social network analysis of the retweets of 215 authorities linked to the European External Action Service is conducted to identify the communication flow and the most influential actors. The results corroborate what the crisis communication literature anticipates. As the pandemic evolved, strategic crisis narratives became more consistent, and the diplomatic network less hierarchical and centralized. After an undetermined start, the COVID-19 crisis was ultimately rationalized as a challenge that reaffirmed the EU’s functionality and values. During the acute phase of the crisis, diplomats were less spontaneous, since their content was more dependent on their superiors, but in later stages they produced proportionally more original content themselves. Therefore, the findings suggest, first, that the EU’s performance on Twitter became more competent over time, and second, a potential correlation between narratives and networks: better defined strategic narratives seem to indicate a more genuine digital diplomacy.